Mathematical Proficiency in Adolescents with ASD. - Cohen, O.; Sukenik, N. (Journal of Autism & Developmental Disorders, 2026)
This study aimed to investigate the mathematical abilities of adolescents with Autism Spectrum Disorder (ASD) compared to typically developing (TD) peers, focusing on procedural thinking, arithmetic comprehension, and algebraic technique. Sixty-seven adolescents (31 with ASD, 36 TD) participated in the study. A comprehensive mathematics skills test, incorporating oral and written components, was individually administered to assess abilities across three main mathematical domains. The study employed a mixed-methods approach, combining quantitative analyses of group differences with qualitative assessments of response patterns. Significant differences were observed between ASD and TD groups across most mathematical measures, with TD adolescents generally outperforming those with ASD. Large effect sizes were noted in procedural thinking and algebraic procedures. However, no significant differences were found in word problem-solving. Within the ASD group, considerable variability was observed, with some individuals demonstrating age-appropriate mathematical abilities while others showed consistently low performance across all domains. The study highlights the complex nature of mathematical abilities in adolescents with ASD, characterized by significant group differences and within-group variability. These findings highlight the importance of individualized approaches in mathematical education for adolescents with ASD and emphasize the need for early identification and targeted interventions to address specific challenges in mathematical learning.